2019
DOI: 10.1007/s11130-019-00760-8
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Shows Antidiabetic Properties that Are Species-Specific: Effects on Enzyme Activity Inhibition and Starch Digestion

Abstract: Despite considerable research the evidence around the antidiabetic properties of cinnamon remains equivocal, and this may be due to varietal differences which is an aspect that is understudied. This study systematically compared the anti-hyperglycaemic properties of the four major commercial cinnamon types used around the world (Chinese; Cinnamomum cassia [CC], Indonesian; C. burmanii [IC], Vietnamese; C. loureirii [VC], and Ceylon; C. zeylanicum [SC]). LC-MS analysis showed distinct diffrences in the phytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…238 C. burmanii, Vietnamese; C. loureirii and Ceylon; C. zeylanicum showed great potential to suppress the formation of AGEs. 239 In diabetic rats, cinnamon and its active component procyanidin-B2 (PCB2) inhibited AGE accumulation and ameliorated AGE-mediated pathogenesis of diabetic nephropathy. 240 It has also been reported that the procyanidin-B2 fraction has the physiological significance of delaying diabetic cataracts by repressing AGEs in diabetic rats.…”
Section: Improvement Of Diabetes Complicationsmentioning
confidence: 99%
“…238 C. burmanii, Vietnamese; C. loureirii and Ceylon; C. zeylanicum showed great potential to suppress the formation of AGEs. 239 In diabetic rats, cinnamon and its active component procyanidin-B2 (PCB2) inhibited AGE accumulation and ameliorated AGE-mediated pathogenesis of diabetic nephropathy. 240 It has also been reported that the procyanidin-B2 fraction has the physiological significance of delaying diabetic cataracts by repressing AGEs in diabetic rats.…”
Section: Improvement Of Diabetes Complicationsmentioning
confidence: 99%
“…All cinnamon types showed potent species-speci c effects on starch digestion enzyme activity inhibition. C. cassia was most effective against α-amylase and all tests strongly inhibited α-glucosidase when compared to acarbose 25 . Natural agents that slow carbohydrate absorption may mimic the protective effect of acarbose.…”
Section: Discussionmentioning
confidence: 95%
“…and many medicinal values including antitumor, anti‐inflammatory, analgesic, anti‐diabetic, anti‐obesity, antibacterial, antiviral, cardiovascular protective, cytoprotective, neuroprotective, immunoregulatory effects, and anti‐tyrosinase activity (Zhang et al., 2019). C. cassia was most effective against α‐amylase and all tests strongly inhibited α‐glucosidase when compared to acarbose (Hayward et al., 2019). Natural agents slowing carbohydrate absorption may mimic the protective or preventative effect of acarbose.…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical studies in humans also proved its effect against type 2 diabetes [9, 10]. Hayward et al [11] compared the anti-hyperglycaemic properties of the four major commercial cinnamon types used around the world namely Cinnamomum cassia (Chinese cinnamon), C. burmanii (Indonesian cinnamon), C. loureirii (Vietnamese cinnamon) and C. zeylanicum (Ceylon cinnamon). Among them, C. zeylanicum showed the greatest potential to inhibit the formation of advanced glycation end products (AGEs) during digestion thus proved its antihyperglycemic activity.…”
Section: Introductionmentioning
confidence: 99%